The semiotics of Emoji - Danesi, Marcel, 1946- (Bloomsbury advances in semiotics., 2017)
The Semiotics of Emoji looks at what is officially the world's fastest-growing form of communication. Emoji, the colourful symbols and glyphs that represent everything from frowning disapproval to red-faced shame, are fast becoming embedded into digital communication. Controlled by a centralized body and regulated across the web, emoji seems to be a language: but is it? The rapid adoption of emoji in such a short span of time makes it a rich study in exploring the functions of language. Professor Marcel Danesi, an internationally-known expert in semiotics, branding and communication, answers the pertinent questions. Are emoji making us dumber? Can they ultimately replace language? Will people grow up emoji literate as well as digitally native? Can there be such a thing as a Universal Visual Language? Read this book for the answers -- publisher's description.